Analysis of Customer Satisfaction Based on Product Quality at Segitiga Bermuda Coffee and Eatery Pamulang - Tifani, Rachel Angela; Pasaribu, Veta Lidya Delimah (Formosa Journal of Multidisciplinary Research, 2024)
This research is motivated by the phenomenon of significant growth in coffee shop businesses that compete with each other to reach consumers. Therefore, it is necessary to formulate an appropriate strategy to survive in attracting market share. The purposes of this research is to: (1) identify the strategies used by companies in determining product quality to create consumer satisfaction, (2) to find out attributes that customers consider important to achieve customer satisfaction of the quality product, (3) to find out strategies for developing consumer satisfaction at Segitiga Bermuda Coffee and Eatery Pamulang. The type of this research is Descriptive Qualitative method. Researchers conducted in depth interviews with Segitiga Bermuda Customers, Observation, and Study Leteratur. The data analysis technique used is SWOT analysis to be able to express the company’s internal and external conditions as well as evalute in order to develop product quality  in order to create consumer satisfaction. The result of research conducted based on data analysis show that consumers have received what they expected from product quality. However, at certain periods the company must carry out monitoring again through surveys because consumers satisfaction with the product must be observed or anlayzed regularly during the specified period.